RANCANG BANGUN ALAT DESALINASI AIR LAUT SKALA LAB TIPE MULTI STAGE FLASH - Dwi Rahmalina; Erlanda Augupta Pane; Raka Chandra Herdyana; Dio Pratama Dirgahayu Putra; Reza Abdu Rahman (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2022)
Desalination is a water treatment process to separate salt from a salt solution to produce drinking water or water with low TDS. The technology used uses Thermal Energy as a heat source using the Phase Change Material (PCM) principle. This research uses the Pahl-Beitz design method. The results of the design are based on the value of the variant in variant 1 is 3.36, variant 2 is 3.22 and variant 3 is 3.14, and the selected value is variant 1 with a weight value of 3.36. The selected variant is tested for strength against heat on the components to ensure it is safe and can be carried out in the manufacturing stage. The process of making seawater desalination tools is carried out using the DFMA design method, each process of working on the tool refers to the Standard Operation Procedure that has been determined and the assembly process is carried out sequentially according to the Operation Process Chart. The manufacture of seawater desalination equipment is carried out by many processes, from material cutting to welding and component assembly. The data from the calculation analysis on the pipe, obtained the axial stress value of 3811.96kN/m2. The results of the calculation of stress due to pressure in the pipe of 317.5kN/m2 circumferential stress of 635kN/m2. The minimum thickness of the pipe is 2.0875mm. the calculation of the circular pipe flow velocity is 9.96m/s. The components in this tool consist of a seawater desalination tool with 41 stages of the process.